The age of catastrophe a history of the West, 1914-1945 - Winkler, Heinrich August (Yale University Press, 2015)
Characterized by global war, political revolution and national crises, the period between 1914 and 1945 was one of the most horrifying eras in the history of the West. A noted scholar of modern German history, Heinrich August Winkler examines how and why Germany so radically broke with the normative project of the West and unleashed devastation across the world. In this total history of the thirty years between the start of World War One and the dropping of atomic bombs on Hiroshima and Nagasaki, Winkler blends historical narrative with political analysis and encompasses military strategy, national identity, class conflict, economic development and cultural change. The book includes astutely observed chapters on the United States, Japan, Russia, Britain, and the other European powers, and Winkler's distinctly European perspective offers insights beyond the accounts written by his British and American counterparts. As Germany takes its place at the helm of a unified Europe, Winkler's fascinating account will be widely read and debated for years to come.